PENGARUH KOMPETENSI DAN KONFLIK KERJA TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MODERATING PADA KARYAWAN CV. AVINDO MANDIRI KABUPATEN SITUBONDO - Husna, Arifi Auliyah; Hamdun, Edy Kusnadi; Anshory, Muhammad Iqbal (Fakultas Ekonomi dan Bisnis, 2024)
An Situbondo Regency is one of the small regencies located in the eastern part of the island of Java. This district has inadequate infrastructure, including companies that have been built and established. One of the companies that stands out is CV, an individually owned company that manages event organizer and wedding organizer services. This study analyzed the effect of competence and work conflict on employee performance with work motivation as a moderating variable in CV Avindo Mandiri Situbondo Regency employees. The number of samples used in this study was 52 CV—Avindo Mandiri Situbondo Regency employees, other than the leadership. The sampling technique used was the Saturated Sampling Technique. This study's data analysis and hypothesis testing used the Structural Equation Model - Partial Least Square (PLS-SEM). The direct influence hypothesis test results using the Smart PLS 3.0 application show that the variable Competence on Employee Performance CV. Avindo Mandiri has a significant positive effect, the effect of work conflict on employee performance CV. Avindo Mandiri has a negative effect that is not significant—competency variables on employee performance CV. Avindo Mandiri mode, rated by Work Motivation, has a negative effect that is not significant. The variable work conflict is on employee performance CV. Avindo Mandiri, with moderated Work motivation, has a positive effect that is not significant.